A Great King at Mycenae. An Argument for the wanax as Great King and the lawagetas as vassal ruler. - Kelder, J (Lockwood Press, 2008)
The position of the wanax in the Mycenaean world is often perceived as that of a local monarch, ruling from a palatial centre and controlling (to a large extent) the surrounding region. Territorially speaking, that region does generally not exceed its natural border, such as large rivers or major mountain ranges, and can be compared in size to most modern day nomes / provinces. Although these Mycenaean Kingdoms in a cultural respect appear to have been essentially the same, most archaeologists consider this the result of trade / exchange and sheer proximity to each other, rather than anything else. The argument in this article is twofold: first, it is argued that the view described above is essentially based on a circular argument, spawned from a desire to denounce the – in the 19th and early 20th century ruling – Homeric paradigm of Mycenaean Greek unity (to whatever extent). Second, this article argues that, whilst the modern view of Mycenaean political fragmentation is not necessarily flawed, a case in favour of a ‘unified Mycenaean world’ is at least equally persuasive. Moreover, that view would be corroborated by Hittite and Egyptian texts, indicating larger political entities on the Greek mainland during the 15th to 13th century BC. This article focuses on archaeological and Linear B evidence; ‘external’ sources, such as the above mentioned Egyptian and Hittite texts, will only be referred to obliquely and as supplements to ‘autochthonous’ evidence.